Zodiacal exoplanets in time – XI. The orbit and radiation environment of the young M dwarf-hosted planet K2-25b. (14th August 2020) - Gaidos, E; Hirano, T; Wilson, D J; France, K; Rockcliffe, K; Newton, E; Feiden, G; Krishnamurthy, V; Harakawa, H; Hodapp, K W; Ishizuka, M; Jacobson, S; et al.
ABSTRACT: M dwarf stars are high-priority targets for searches for Earth-size and potentially Earth-like planets, but their planetary systems may form and evolve in very different circumstellar environments than those of solar-type stars. To explore the evolution of these systems, we obtained transit spectroscopy and photometry of the Neptune-size planet orbiting the ≈650-Myr-old Hyades M dwarf K2-25. An analysis of the variation in spectral line shape induced by the Doppler 'shadow' of the planet indicates that the planet's orbit is closely aligned with the stellar equator ($λ =-1.7_{-3.7}^{+5.8}$ deg), and that an eccentric orbit found by previous work could arise from perturbations by another planet on a coplanar orbit. We detect no significant variation in the depth of the He i line at 1083 nm during transit. A model of atmospheric escape as an isothermal Parker wind with a solar composition shows that this non-detection is not constraining compared to escape rate predictions of ∼0.1 M⊕ Gyr −1 ; at such rates, at least several Gyr are required for a Neptune-like planet to evolve into a rocky super-Earth.